2018
DOI: 10.1155/2018/9591502
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of an Isolated Dislocation of the Scaphoid in a Lesser Arc Injury and a Review of the Literature

Abstract: Isolated dislocations of the scaphoid are extremely uncommon injuries and are often associated with significant ligamentous failures. Since scaphoid dislocations typically present with associated carpal fractures, few cases of isolated dislocations of the scaphoid exist in the literature. The proposed treatment options in the literature range from closed reduction and casting to open reduction and internal fixation. We present the case of a 41-year-old male with an isolated scaphoid dislocation in whom open re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A literature search was performed using isolated or solitary dislocation of the scaphoid as key words; this search identified 58 cases reported in English since the first isolated scaphoid dislocation was reported in 1930[ 1 , 2 , 6 - 42 ]. The classification of isolated scaphoid dislocation is based on the description by Leung et al [ 2 ], and can be used to distinguish dorsal dislocation from dorsal intercalated segment instability caused by scapholunate ligament injury, even though the treatment options for these two injuries may be the same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature search was performed using isolated or solitary dislocation of the scaphoid as key words; this search identified 58 cases reported in English since the first isolated scaphoid dislocation was reported in 1930[ 1 , 2 , 6 - 42 ]. The classification of isolated scaphoid dislocation is based on the description by Leung et al [ 2 ], and can be used to distinguish dorsal dislocation from dorsal intercalated segment instability caused by scapholunate ligament injury, even though the treatment options for these two injuries may be the same.…”
Section: Discussionmentioning
confidence: 99%
“…Possible complications of isolated scaphoid dislocation might be degenerative joint and carpal instability, which are likely to be seen in neglected cases[ 6 , 7 ]. However, in this literature review, 4 of the 48 cases showed scapholunate diastasis during the follow-up after open reduction, although in none of them was diagnosis delayed[ 16 , 21 , 33 , 38 ].…”
Section: Discussionmentioning
confidence: 99%